Individual work performance, mental well-being, work engagement and burnout among Naim Land Sdn Bhd. employees / Stephanie Pilipin - Pilipin, Stephanie (Faculty of Business and Management, 2015)
This study was conducted to examine the individual work performance, mental well being, work engagement and burnout among Naim Land Sdn. Bhd. employees. The study aimed to find out the level of individual work performance, mental well-being, work engagement and burnout among Naim Land Sdn. Bhd employees. It was aimed to identify the relationship between individual work performance and mental well-being, relationship between individual work performance and work engagement, relationship between individual work performance and burnout, relationship between mental well being and work engagement, relationship between mental well-being and burnout and relationship between work engagement and burnout. This study adopts quantitative approach with collected samples of 80 respondents through direct questionnaires method. SPSS statistical tool was used to test the descriptive statistics. Results show employees at Naim Land Sdn. Bhd. have a high level of work engagement, followed by mental well being and individual work performance. Burnout was reported to be low. The relationship between IWP, Mental Well-Being, Work Engagement and Burnout were also discussed in Chapter 4. For relationship between IWP and Mental Well-Being, IWP and Work Engagement, IWP and Burnout are positively and moderate, and positively and low relationship as indicated by the value of r except for the third dimension in the IWP where it shows negative and low relationship. Implications, limitations and recommendations for future research are also discussed.